Calcium phosphate‐based composite cement: Impact of starch type and starch pregelatinization on its physicochemical properties and performance in the vertebral fracture surgical models in vitro. Issue 12 (24th May 2021) - Tian, Yixing; Liu, Huiling; He, Linwei; Zhang, Rui; Lu, Qifeng; Liu, Chun; Dang, Ningqi; Hu, Hui; Ma, Xuan; Chen, Dandan; Sun, Haolin; Zhou, Huan; et al.
Abstract: Calcium phosphate cement (CPC) modified with native and pregelatinized normal corn and waxy maize starches was studied. Effects of starch pregelatinization and starch type on the physicochemical properties of CPC were investigated. CPC modified with pregelatinized normal corn starch (CPB‐PNC) or pregelatinized waxy maize starch (CPB‐PW) was evaluated by two vertebral fracture surgical models in vitro . Both granular and pregelatinized starches significantly improved the setting times and injectability of CPC, but only the pregelatinized starches improved the anti‐collapsibility and compressive strength of CPC significantly. CPB‐PW, whose micro‐structure was compact and uniform, showed the best physicochemical properties. Addition of starch did not inhibit the hydro‐reaction of CPC. Unmodified CPC had very poor dispersibility and could not apply in the tests of the surgical models. Pregelatinized starch especially waxy maize starch improved the dispersibility of CPC and showed good dispersion area, volume, improved pull‐out force and maximum torque in the Sawbones sponge model. Similarly, in the minimally invasive kyphoplasty model, CPB‐PNC and CPB‐PW could disperse in the osteoporotic sheep vertebrae and improve the compressive strength of the sheep vertebral body. In conclusion, starch pregelatinization and starch botanical source affect the physicochemical properties of CPC significantly. Bone cements modified by different starches also performed differently in surgical models for osteoporotic vertebral fracture. Pregelatinized waxy maize starch may be a better candidate for CPC modification comparing to the pregelatinized normal corn starch.